2014
DOI: 10.3171/2013.11.spine13402
|View full text |Cite
|
Sign up to set email alerts
|

High cervical arteriovenous fistulas fed by dural and spinal arteries and draining into a single medullary vein

Abstract: Object The authors previously reported a case of complex arteriovenous fistula (AVF) at C-1 with multiple dural and spinal feeders that were linked with a common medullary venous channel. The purpose of the present study was to collect similar cases and analyze their angioarchitecture to gain a better understanding of this malformation. Methods Three such cases, affecting 2 males and 1 female in their 60s who had presented with hematomyelia (2) or progressive myelopathy (1), were treated surgically, and the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…In recent reports, the angiographic findings of CCJ AVFs were interpreted as the coincidental development of DAVF and PAVF. 5,11,13 In the present study, we found that more than half of the CCJ AVFs (35 [59%] of 59 lesions) were fed by both the radiculomeningeal arteries from the VA and the spinal pial arteries from the ASA and/or LSA. Moreover, 10 lesions with these 2 kinds of feeders were imaged with superselective angiography, and these feeders drained into the same vein.…”
Section: Radiculomeningeal and Pial Feeders Of Ccj Avfsmentioning
confidence: 46%
“…In recent reports, the angiographic findings of CCJ AVFs were interpreted as the coincidental development of DAVF and PAVF. 5,11,13 In the present study, we found that more than half of the CCJ AVFs (35 [59%] of 59 lesions) were fed by both the radiculomeningeal arteries from the VA and the spinal pial arteries from the ASA and/or LSA. Moreover, 10 lesions with these 2 kinds of feeders were imaged with superselective angiography, and these feeders drained into the same vein.…”
Section: Radiculomeningeal and Pial Feeders Of Ccj Avfsmentioning
confidence: 46%
“…The angioarchitectural characteristics of arteriovenous fistulas can, however, be hard to accurately define; thus, classifying them as such can represent a challenge. The authors of one case series postulate that some previously reported cases of apparent high cervical dural fistulas may in fact have been complex forms with, for example, additional supply from the spinal arteries,1 and perimedullary fistulas were most likely misclassified as dural fistulas in a large 2006 review 6…”
Section: Discussionmentioning
confidence: 99%
“…An initial diagnosis of a cervical dural arteriovenous fistula was made on the basis that there appeared to be no continuity between the feeding artery and the anterior or posterolateral spinal arteries. This would be in keeping with a dural fistula, for which the feeding vessel is a radiculomeningeal artery that does not usually supply the spinal arteries,1 versus a perimedullary fistula on the pial surface which is supplied by the spinal arteries 2. Subsequent review of the angiographic findings, however, casts doubt over this assertion.…”
Section: Case Presentationmentioning
confidence: 96%
“…[ 2 ] However, DAVFs and PAVFs located at the craniocervical junction or cervical regions are associated with an increased incidence of SAH and cranial nerve dysfunction. [ 1 5 ] The concurrence of DAVFs and PAVFs is exceedingly rare, and there are only 11 reports of such cases occurring at the craniocervical junction or cervical region[ 9 11 ] and 4 such cases located at the thoracolumbar region. [ 3 6 8 10 ] Sato et al .…”
Section: Discussionmentioning
confidence: 99%